Optimizing Enterprise Architecture: The Role of TOGAF in Driving Organizational Transformation - Andi Anggi Kemalasari; Sutrisno (Indonesian Journal of Enterprise Architecture, 2024)
The rapid development of technology in this era does not rule out the possibility that every organization needs information technology as a medium to support the organization in achieving its goals. In the implementation of TOGAF, PT. Pos Indonesia follows the steps specified by the framework. First, they conduct an indepth analysis of the needs and goals of the company. It involves understanding the organization's vision, mission, and business strategy as well as identifying areas of improvement that can result through implementing enterprise architecture. PT. Pos Indonesia conducts an inventory of its current architectural assets and resources, including IT infrastructure, applications, data, and business processes. It helps them in understanding the strengths and weaknesses present in their enterprise architecture. During the implementation phase, PT. Pos Indonesia implements the changes identified in the transformation plan. They integrate new technology solutions, improve business processes, and migrate data according to the desired enterprise architectural design. PT. Pos Indonesia conducts continuous monitoring and management of their corporate architecture. They ensure that the architecture is constantly relevant to business and technological changes taking place, and involve necessary updates and adjustments. Through the implementation of TOGAF, PT. Pos Indonesia can improve operational efficiency, increase adaptability to change, and accelerate their transformation initiatives. The framework assists them in integrating new technologies, improving service delivery, and increasing value for their customers.